Graphene-modified C/C composites for enhanced directional thermal conductivity - Shanyong Song; Xinyang Li; Chen Shen; Ming Li; Xiaoye Hu; Zhen Jin; Zhulin Huang (Journal of Materials Research and Technology)
Incorporation of high thermal conductive materials with carbon fiber (CF) reinforced carbon matrix (C/C) composites is an effective strategy for enhancing their overall thermal conductivity. However, this approach often disrupts the orientation of graphite within the carbon matrix. In this study, graphene-modified C/C composites with preferred orientation were constructed by decorating CF with graphene oxide (GO), followed by liquid phase impregnation of mesophase pitch, carbonization, and graphitization. The orientation of mesophase pitch derived-graphite carbon matrix was preserved after the aligned decoration of GO on the CF, due to the chemical bonding between GO and polydopamine (PDA) on the CF surface. Importantly, the moderate GO decoration amount increased the overall graphitization degree of the C/C composites, while simultaneously strengthening their microstructural anisotropy. As a result, the in-plane thermal conductivity of the C/C composites increased from 183.09 to 210.97 W/(m·K) when 2.4 wt% GO was decorated on the CF surfaces. The finite element analysis results also indicate that the in-plane thermal conductivity was enhanced with GO decoration. In addition, the tensile strength of the C/C composites increased from 12.76 to 16.52 MPa. This work provides valuable insights into the design and fabrication of C/C composites with enhanced directional thermal conductivity and mechanical properties.